2009
DOI: 10.1093/rheumatology/kep313
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide synthase increases secretion from inflamed salivary glands

Abstract: Objective. Salivary gland secretion is dependent on cholinergic stimulation via autonomic nerves and calcium signalling in acinar cells. Secretory dysfunction associated with SS may be partly caused by the damaging effects of increased glandular concentrations of nitric oxide (NO) derived from up-regulation of inducible NO synthase (iNOS) that accompanies glandular inflammation. The present study examines the effects of increased iNOS expression on salivary gland secretory function.Methods. The inflammogen lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
1
17
1
Order By: Relevance
“…These experiments verified that innate immune activation interferes with the secretory ability of the SMGs, independent of the invasive immune cell signal. Findings from the current experiments, combined with other studies which demonstrated the little correlation between secretory hypofunction and immune cellular infiltration, strongly implicate an alternative impairment mechanism by which the SG epithelial cells endogenously respond to injury and cease secretion.…”
Section: Discussionsupporting
confidence: 72%
“…These experiments verified that innate immune activation interferes with the secretory ability of the SMGs, independent of the invasive immune cell signal. Findings from the current experiments, combined with other studies which demonstrated the little correlation between secretory hypofunction and immune cellular infiltration, strongly implicate an alternative impairment mechanism by which the SG epithelial cells endogenously respond to injury and cease secretion.…”
Section: Discussionsupporting
confidence: 72%
“…The supersensitivity is thought to reflect changes beyond the receptor level rather than at the recognition site (15). It was recently shown that the secretory response to intravenous methacholine is transiently increased in the inflamed rat submandibular gland (at 3 and 24 h, but not at 96 h) after the intraductal injection of the inflammogen lipopolysaccharide (17). This finding is in contrast to the results of other studies on the inflamed rat submandibular gland, which showed decreased secretory responses to secretogogues during a similar period of time after exposure to lipopolysaccharide (18, 19).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that iNOS could be the critical determinant in the development of diabetes complications in humans because the vascular deterioration observed in diabetes is proven to be, at least partially, attributed to the pathological production of increased levels of superoxide that stimulates the overgeneration of NO by iNOS (12, 13). Immunohistochemical analysis revealed an up‐regulation of iNOS expression in the rat submandibular gland, associated with Sjögren’s syndrome (14), as well as in the gingival tissues of rat (15) and of humans with periodontitis (16).…”
mentioning
confidence: 99%